The Use of Vacuum Devices as Adjuvant Therapy before and after Penile Curvature Surgery in Patients Affected by La Peyronie’s Disease: Results from a Comparative Study - Tommaso Cai; Marco Capece; Carlo Ceruti; Daniele Tiscione; Marco Puglisi; Paolo Verze; Paolo Gontero; Alessandro Palmieri (Clinics and Practice, 2023)
Background: Peyronie’s disease (PD) represents a challenging urological disease, due to not optimal post-operative surgical outcomes. We aim to retrospectively evaluate if vacuum erection device (VED) treatment before penile curvature surgery is able to improve post-operative surgical outcomes. Methods: All enrolled patients were assigned to the following groups: (a) the treatment group: VED treatment (three times per week) starting 3 months before surgery and (three times per week) one month after surgery; and (b) the control group: VED treatment (three times per week) one month after surgery. Follow-up urologic visits were scheduled for 3 and 6 months after surgery, and the two groups were compared. Results: A total of 38 patients were enrolled (median age 67 years, 57–74, IQR): 20 in the treatment group and 18 in the control group. At the follow-up visits, the two groups were different in terms of IIEF-5 (26 vs. 24; p = 0.02), “yes” to SEP2 and 3 (85% vs. 55%; p < 0.001, 85% vs. 50%; p < 0.001, respectively), and PDQ (−16 vs. −11; p = 0.03). Complete correction of penile curvature was achieved in 36 patients (94.7%). In the treatment group, no hourglass deformity was reported, whereas one patient reported a mild hourglass deformity in the control group. In the treatment group, we obtained a longer total penile length (median +1.5 cm). The overall satisfaction rate was 98% in the treatment group and 96% in the control group. Conclusions: The VED treatment before penile curvature surgery in patients affected by PD was able to improve surgical outcomes.